2023
DOI: 10.1111/1468-0009.12626
|View full text |Cite
|
Sign up to set email alerts
|

Without Affordable, Accessible, and Adequate Housing, Health Has No Foundation

Abstract: Today's housing disparities are rooted in the increasing commodification of housing that has taken precedence over the need for shelter, a basic human right. With rising housing costs across the country, more residents are finding their monthly income going to rent, mortgage payments, property taxes, and utilities, leaving little for food and medication. Housing is a determinant of health, and with increasing housing disparities, action must be taken to ensure no individual is displaced, communities remain int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Studies have shown that patients with lower socioeconomic status have less access to rehabilitation services, which are essential for promoting poststroke self-care performance (Isenberg et al, 2023; Kapral et al, 2002; Marshall et al, 2015). Moreover, inadequate income and housing have been identified as critical factors influencing self-care (Mehdipanah, 2023; Stulberg et al, 2021). Occupational therapy practitioners must recognize how a mild stroke survivor’s neighborhood environment affects their self-care performance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients with lower socioeconomic status have less access to rehabilitation services, which are essential for promoting poststroke self-care performance (Isenberg et al, 2023; Kapral et al, 2002; Marshall et al, 2015). Moreover, inadequate income and housing have been identified as critical factors influencing self-care (Mehdipanah, 2023; Stulberg et al, 2021). Occupational therapy practitioners must recognize how a mild stroke survivor’s neighborhood environment affects their self-care performance.…”
Section: Discussionmentioning
confidence: 99%